The monitoring of worker health after exposure to biological fluids - Leila Maria Mansano Sarquis; Vanda Elisa Andres Felli (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
Introducion The exposition of the workers of health to the biological occupational risk is a reality very argued in the last decades. Still, exactly when the accidents are notified and the workers guided for the accomplishment of the protocol of biological monitoring, not adhesion on the part of these worker's.1,2,3 This great exposition of the workers of health to the biological fluids if must in part to the nature of the work that carry through e, more emphatically to the forms of organization of these worker's.4 Objective: to subsidize the proposition of a intervention programme for health workers exposed to biological fluids; to describe these workers; to hold the attention to their feelings and perceptions; to identify the difficulties experienced in the environment and to analyze strategies for minimization of these exposure. Methodology: The focus group technique was elected for collecting the data and the subject discourses were discussed and submitted to thematic analysis, of which emerged four empiric categories. Main results: The quantitative analysis showed the female gender (93%), among nursing workers (60%); The hospital was the place of work that most happened the exposure (86%); the most common type of accident was with puncture cutting instruments; the inappropriate usage of EPIs was found in 40% of the accidents; 14% of workers, hasn't had the vaccinal scheme completed and 73% of the subjects made the entire monitoring without any serum conversion. The qualitative analysis of the four empiric categories enabled evident that the first one - occupational exposure - , happened by the inappropriate and/or lack of supply resources; inadequate human resources; type of work made at the work units and risk behavior of the workers. The second one - the feelings involved - identified the fear of disease and chieftainship, worry, indecision; anger and disgust; guilty and insecurity. The third - the causes of abandon the follow-up - occur by the discredit of seriousness and by operational difficulties experienced by the workers. The fourth category - the institutional and personal strategies - was proposed by the subject research. Aiming prevention, intervention and follow-up of these workers were made proposals and Recommendations to the Health Service composed firstly by a Programme of intervention and follow-up of workers exposed to biological fluids with some recommendations for treatment and follow-up of workers and by a Matrix Recommendations in health operation, categorizing activities to be carried out with service managers and their health teams in four extents: administrative, assistance, teaching and research. Conclusion: it is apprehended with the study that the way the work in health organizes itself is the main determinant of workers exposure to biological fluids. The study also shows the necessary and important articulations among institutions and units of attention towards workers health and secretariat of state in aid of prevention of these accidents with health workers.